Comprehensive evaluation of medical students' teamwork skills - Panagiotopoulou, Eirini-Kanella; Bakirtzis, Minas; Vavanou, Eirini; Ntonti, Panagiota; Labiris, Georgios (Medical Research Archives, 2022)
Background: Teamwork plays a pivotal role in patient care and safety promotion. "TeamSTEPPS Teamwork Attitudes Questionnaire" (T-TAQ) aims to the assessment of attitudes of care providers regarding teamwork when enrolled in a series of TeamSTEPPS-based scenarios; among them, cooperation in mass casualty scenarios, medical error simulations, and other virtual learning experiences. However, the use of T-TAQ could be expanded into the evaluation of medical students' collaboration capacity in a series of educational tasks such as the management of a simulated clinical scenario within the context of a university course.   Aim: To prospectively explore teamwork performance of Greek medical students in simulated clinical scenarios in the undergraduate course of Ophthalmology.   Methods: This is a prospective, descriptive study. All fifth-year medical students attending the undergraduate course of Ophthalmology were asked to form teams, each one had to select a simulated clinical ophthalmological scenario and present the outcomes of their project. Scenarios were case reports from patients that visited the outpatients’ service of the Department during the previous six months. Α custom Greek version of the T-TAQ containing 29 5-scale Likert-type items in five subscales (team structure, leadership, situation monitoring, mutual support and communication) was used to evaluate students’ attitudes on the overall procedure. T-TAQ scores were evaluated with gender, residence and other parameters.   Results: 102 students participated in this project. Students presented average total T-TAQ score (3.48±0.99) with non-significant differences regarding gender (p=0.38) and residence (p=0.58). Non-significant differences were detected for all subscale scores, as well (all p>0.05). Significant correlation was detected between team project performance and team structure (R 2 =0.375, p=0.04), mutual support (R 2 =0.463, p=0.02), and total T-TAQ score (R 2 =0.349, p=0.05). Additionally, readiness to form teams showed significant correlation with total T-TAQ score (R 2 =0.512, p<0.01) and project performance (R 2 =0.444, p=0.01). However, non-significant correlation was identified between T-TAQ score and students’ final grades in the Ophthalmology course (R 2 =0.015, p=0.28).   Conclusion: Greek medical students demonstrated average T-TAQ scores. Medical schools should also focus on the development of collaboration skills for their medical students and possibly enroll teamwork initiatives to their curricula.